THE FRUITS OF GOJI (LYCIUM BARBARUM L.) ARE A PROMISING RAW MATERIAL FOR PRODUCTION OF ZEAXANTHIN (E 161H) - Tereshkova E.S.; Batashov E.S.; Sevodin V.P. (Техника и технология пищевых производств, 2015)
Nowadays the xanthophylls lutein and zeaxanthin are used, in ophthalmic preparations for the prevention of age-related degeneration of the retina and cataracts. It is known that the carotenoids enter the body with plant foods or food additives derived from plant or microbial raw materials. They can be also obtained by means of chemical synthesis. Lutein is used in food industry as a colorant. Its source are the flowers of marigold ( ), which is are a common plant. Zeaxanthin is less available than lutein, so the search for new sources with a high content of xanthophyll is relevant. The plants, accumulating zeaxanthin and its esters are the fruits of Goji ( ), known in Chinese medicine as the Goji berry. In the berries zeaxanthin is present mostly in the esterified form, in the form of zeaxanthin dipalmitate. Water- and oil-soluble extracts of dried Goji berries (fruit of Wolfberry, ) have been obtained as a result of the experiment. The conditions of the chromatographic analysis were described with a thin layer chromatography (TLC) method and a high performance liquid chromatography (HPLC) method, and with the preparative separation of zeaxanthin with the method of column chromatography on aluminium oxide. Ultraviolet (UV) spectra of the samples obtained show that the absorption maximum of zeaxanthin standard and that of the sample obtained from the berries of Goji are the same. The optimum conditions to carry out saponification have been established. The content of xanthophyll in extracts is 13.5 mg/100 before saponification, 62 mg/100 g after saponification, 44 mg/100 g in purified ones. An aqueous extract of the berries can be used as a raw material for obtaining biologically active substances (BAS) or can be used as biologically active additives (BAA). It can be used to create a balanced xanthophyll drugs as well.